Role of training in Vietnamese small and medium-sized companies. - Loh, Huu Chong. (2008)
This report aims to understand the role of training in Vietnamese Small and Medium sized Enterprises (SMEs). Vegastar is chosen to be the company of study as they are attempting to bring high-end technologies into Vietnam. This interesting feature makes Vegastar a good research topic, as it is a challenge to introduce new technologies into a developing country such as Vietnam. This also sets up the basis of the research interest of how training can help such SME to handle new technologies. Thus, a study of how Vegastar is coping with a new technology in view of the training provided by the principal is covered. The team also looked at the training provided by Vegastar to customers.